Pancreatic Kaposiform Hemangioendothelioma Not Responding to Sirolimus - Paloma Junco Triana; Mariela Dore; Vanesa Cerezo Nuñez; Javier Gomez Jimenez; Miriam Ferrero Miguel; Mercedes González Díaz; Joan Novo Ricardo; Ane Andres; Manuel Lopez Santamaria; Juan Carlos Lopez-Gutierrez (Georg Thieme Verlag KG, 2017)
Abstract Background Kaposiform hemangioendothelioma (KHE) is a vascular tumor frequently associated with Kasabach-Merritt phenomenon (KMP), characterized by severe thrombocytopenia and consumptive coagulopathy. Visceral involvement in KHE is rare. In our recent experience, sirolimus has shown to be an effective treatment in cutaneous KHE, becoming indeed the treatment of choice in KMP. We report a case of pancreatic KHE associated with KMP and refractory to sirolimus. Case Report A 4-month-old infant is referred for obstructive jaundice (10 mg/dL conjugated bilirubin) secondary to vascular pancreatic tumor. Magnetic resonance (MR) and immunohistochemistry were compatible with KHE, but the tumor was considered unresectable. We initiated sirolimus (0.8 mg/m2/12 h) to treat KMP, and interventional radiology was performed for percutaneous biliary diversion. This procedure prompted KMP (platelets: 51,000/µL). Sirolimus treatment for 7 days showed no effect; therefore, we started our VAT protocol (vincristine/aspirine/ticlopidin) with great response after 10 days (platelets: 3,70,000/µL). Three months later, percutaneous biliary diversion was replaced by a biliary stent. The tumor disappeared leaving fibrosis and dilatation of biliary tract needing hepaticojejunostomy 6 months later. Discussion It is difficult to establish protocols for an unusual presentation of a tumor with different targets. This is a reason collaborative multicenter studies should be performed. Management of obstructive jaundice secondary to a tumor that usually regresses in 10 years is an added challenge; therefore, the management should be led by a multidisciplinary team. Sirolimus treatment in cutaneous KHE has been described as successful in the literature, as well as in our own experience; however, it failed in our first patient with visceral KHE. We need to investigate the different response to pharmacological agents in tumors with similar histopathology, but with visceral involvement.